(untitled) (Revista "Boletín el Conuco", 2023)
Research and dissemination are central elements of science, the central objective of dissemination is to communicate scientific knowledge, using various means. Nothing is more valuable in science than communicating the research process, but above all the results, which will be the spearhead for continuous research and innovation from all aspects of science. The “Boletín el Conuco” Magazine is a fundamental tool for the dissemination and/or dissemination of science, in its different chapters it has published information that is and has been very important for the knowledge society; as well as for end users in favor of an adequate technology transfer exercise.